Selection for improved nitrogen fixation in Glycine max (L.) Merr. and Phaseolus vulgaris L. - Graham, Peter H.; Temple, Steven R. (Springer, 1984)
While symbiotic nitrogen (N2) fixation by G. max and P. vulgaris reduces their need for combined N, N2 fixation under field conditions is rarely maximized. This paper reviews constraints to N2 fixation in these species, then examines the genetic variability recorded for traits affecting N2 fixation and the further work needed in this area. It considers emerging programs for the improvement of N2 fixation in G. max and P. vulgaris and pays particular attention to methodological considerations.